The Relationship Between Culture And Readiness To Accept Transformation In Single-Specialty Hospitals In Tehran - Hasan Abolghasem Gorji; Heshmatollah Asadi; Masoud Roudbari; Ahmad Barati Marnani; Mojtaba Hasoumi; Mohammad Mohseni (Tehran University of Medical Sciences, 2014)
Background and Aim: Readiness to face changes and transformation in health fields is one of the main factors in health organizations' success. The main purpose of the present study was to determine the relation between culture and readiness to accept transformation in single-specialty hospitals. Materials and Methods: Readiness to face changes and transformation in health fields is one of the main factors in health organizations' success. The main purpose of the present study was to determine the relation between culture and readiness to accept transformation in single-specialty hospitals. Results: Studied hospitals had low power distance, high uncertainty avoidance, feminist, collectivist and short-term orientation. There was a significant relation between readiness to accept transformation with factors such as: Power distance (P<0/05, r=-0/236), uncertainty avoidance (P<0/05, r=0/143) and being feminist (P<0/05, r=-0/239). There was no significant relation between readiness to accept transformation with factors such as collectivist and short-term orientation (P>0/05). Conclusion: Low power distance, high uncertainty avoidance and being feminist are effective factors in accepting transformation among studied hospitals' staffs. These staffs are culturally prepared to accept evolution plans.